The use of Takadimi syllable rhythmic reading in improving pupils ability to play music instruments in percussion ensemble / Mohd Zafuan Bakhtar - Bakhtar, Mohd Zafuan (2015)
This action research are using the qualitative study to investigate the effects between two different syllables counting approaches on 28 pupils from 4 Erat class in Sekolah Kebangsaan (2) Simpang Lima, Klang. The goal of this study was to improve pupil ability in playing music instruments in ensemble, by using the Takadimi rhythmic reading approach. During the five weeks lessons pupils will spent time with the researcher and exploring the new rhythmic reading approach and performing on each instruments in ensemble. The pre-test and post-test was being given in early and in the ends of lessons, in order to identify improvement achieved by pupils before and after applying the Takadimi approach in their rhythmic reading exercise, and whether their ability of playing the music instruments had increased. The researcher also made the reflective journal, in order to get full view about an improvement achieved and also to reflect on pupils learning. The data was collected from observations made by researcher and from random interview questionnaire with pupils. Results showed that after using the Takadimi rhythmic reading approach, pupils can play the music instruments more efficiently, and their knowledge about beats and rhythm had increased.